Deskripsi Pemahaman Konsep Calon Guru pada Materi Perancangan dan Pembangunan Laboratorium Kimia Menggunakan Model Discovery Learning - Rody Putra Sartika; Deden Ariansyah; Ilyas Azhari (Universitas Syiah Kuala, 2020)
A prospective chemistry teacher needs to learn about the planning and construction of a chemical laboratory that they can apply when becoming a chemistry teacher at school. This study aims to describe prospective teachers' understanding of discovery learning on the topic of designing and construction of the laboratory. The form of this research is pre-experimental with the design of one shoot case study. Subjects in this study were 21 chemistry education department students of Tanjungpura University conducted. Data collection using measurement techniques with learning outcomes test instruments. Data then were analyzed through steps as follows: 1) data reduction; 2) data presentation; 3) data deduction. The results obtained by understanding the concept of students on the indicators determine and explain the selection of laboratory development positions are in the right criteria. The indicator determines and explains the selection of space for students in the laboratory is in the first category